(untitled) (European Journal of Pure and Applied Mathematics, 2012)
By applying the differential subordination theorem, we further investigate the subclassHn, [,] of functions which are analytic in the unit disk. Several subordination results on a convexÂ function and a incomplete beta function are obtained. Moreover, the function that belongs to theÂ Hn, [,] with a Cauchy-Euler differential equation is also discussed on similar subject. Our resultsÂ extend some earlier works.